Rhodesia—A beginning, not an end - H. Cohn (Intereconomics, 1967)
An embargo is an old, but not always proved instrument of trade policy. In their original sense embargo measures served the prevention of deliveries of militarily important goods to belligerent countries, and thus had a passive and neutral character. Later on, however, they were increasingly used as an economic means of pressure for active prosecution of political objectives. So after World War II the USA e.g.—and under its influence other Western countries—for political reasons, applied embargo measures to restrain trade with East-bloc countries. The strict embargo policy, however, failed owing to the opposition of interested economic circles and the consequent expansion of East-West trade by the socialist countries. Today the further maintenance of embargo lists for deliberations predominantly in the field of defence policy is still disputed as regards its suitability. The embargo against Rhodesia recently decided on by the UN is the application of commercial discriminations as a political means of coercion on a worldwide basis. The following article deals with the impacts and long-term consequences of this massive embargo policy.
Keywords: 330; Un-Sanctions